STRATEGI PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM - Husnul Buairi; Rostati; M. Sobry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving the quality of Islamic educational institutions is a strategic necessity in facing the era of globalization and technological advancement. Islamic educational institutions are not only responsible for producing a generation of intellectual intelligence, but also for developing noble personalities grounded in spiritual values. This article aims to examine strategies for improving the quality of Islamic educational institutions through a modern educational management approach integrated with Islamic principles. The study results indicate that effective strategies include strengthening the institution's vision and mission, improving teacher competency, developing an integrative curriculum, implementing integrated quality management, fostering a religious culture, and enhancing partnerships with the community. By implementing these strategies, Islamic educational institutions can increase their relevance, competitiveness, and contribute positively to national development.